Optimization of Rheological Behaviour and Skin Penetration of Thermogelling Emulsions with Enhanced Substantivity for Potential Application in Treatment of Chronic Skin Diseases - Markus Schmidberger; Ines Nikolic; Ivana Pantelic; Dominique Lunter (MDPI AG, 2019)
Topical formulations are an important pillar in the therapy of skin diseases. Nevertheless, after application the formulation will be exposed to environmental effects. Contact with other surfaces will reduce the available amount of formulation and drug substance. The resulting consequences for therapy range from reduced effects to therapeutic failure. The removed active ingredient also contaminates patients’ environment. The aim of this work was to develop preparations that remain at the application site. These will enhance safety and efficiency and thus improve of skin disease therapies. Therefore, we developed polymer-stabilised emulsions that show thermogelling properties. Emulsions with different methyl cellulose concentrations and macrogols of different molecular weights were investigated. The dispersed phase consisted of nonivamide as the active pharmaceutical ingredient, dissolved in medium-chain triglycerides. Rheological properties, droplet size, substantivity and ex vivo penetration experiments were performed to characterise the developed formulations. Droplet size and rheological parameters were affected by the composition of the preparations. The tested formulations showed benefits in their substantivity compared to a conventional semi-solid cream. We found a residual amount of up to 100% at the application site. The drug levels in viable epidermis were in a therapeutic range. The developed emulsions are a promising vehicle to improve therapy for chronic skin diseases.